2018
DOI: 10.1371/journal.pone.0206451
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity in response to the touch of a hand on the center of the back

Abstract: The aim of this study was to validate the possibility of using functional Near-Infrared Spectroscopy (fNIRS) to measure changes in cerebral blood flow in response to a hand being placed on a participant’s back, and to identify the areas of enhanced activity in the brain. Nineteen female adult volunteers participated in the study. An experienced school nurse touched the center of the participant’s back between the shoulder blades with the palm of her hand. Cerebral blood volume dynamics were measured with a 52-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Evidently, one obvious explanation to this may be simply due to the small sample size of the study lacking statistical power. Morita et al (2018) showed that touch to the back increased oxygenated haemoglobin in the dorsolateral prefrontal cortex. However, data from the present study does show that in comparison to baseline, the right dorsolateral prefrontal cortex does show a mean increase in haemodynamic activity during touch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidently, one obvious explanation to this may be simply due to the small sample size of the study lacking statistical power. Morita et al (2018) showed that touch to the back increased oxygenated haemoglobin in the dorsolateral prefrontal cortex. However, data from the present study does show that in comparison to baseline, the right dorsolateral prefrontal cortex does show a mean increase in haemodynamic activity during touch.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study is one of few that have investigated social touch using fNIRS (Bennett et al, 2014;Morita et al, 2018) whilst majority of studies have used fMRI.…”
Section: Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Touch has been previously shown to improve one’s subjective assessment of physical and psychological function. Physical contact by itself can provide a placebo benefit to patients for reducing both anxiety and pain ( Morita et al, 2018 ). Morita et al.…”
Section: Methodsmentioning
confidence: 99%
“…Repeated activation of CT afferents is associated with better health by reducing sympathetic nervous system activity, increasing parasympathetic nervous system activity, and reducing stress, pain, and anxiety via oxytocin (Heinrichs and Domes, 2008 ; Ishak et al, 2011 ; Quirin et al, 2011 ; Love, 2014 ; Pfeifer et al, 2016 ; Walker et al, 2017 ; Hurlemann and Grinevich, 2018 ; Field, 2019 ; Uvnäs-Moberg et al, 2020 ; Uvnäs-Moberg and Petersson, 2022 ). At the neural level, correlates of social touch are found with the cortical brain regions in the dorsolateral prefrontal cortex (dlPFC) and the OFC, which are also associated with oxytocin projections (Rolls et al, 2003 ; Croy et al, 2016 ; Morita et al, 2018 ; Boehme et al, 2019 ; Field, 2019 ; Chen et al, 2020 ; Uvnäs-Moberg et al, 2020 ). Motor aspects of touch (discriminative touch) significantly predict the activation in the sensorimotor cortex (Rolls et al, 2003 ; Case et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%